Flotation reagents evaluation - Azañero Ortiz, Ángel (1999)
The purpose of this research is to present scientific-experimental methods to correctly evaluate flotation reagents used in mineral concentration. The variables, mathematical equations, methodology and other important parameters that will efficiently quantify the quality of the reagents under evaluation are presented in any mining-metallurgical beneficiation plant.